Creating the valuable: reading as a matter of health and successful parenthood. Issue 1 (2nd January 2019) - Sjödin, Elin Sundström
ABSTRACT: There have been increasing demands to improve Swedish children's reading habits, triggered by poor PISA results in 2013, and public healthcare has stepped in as a strong reading-promoting actor. Drawing on the emerging field of valuation research in STS, the paper explores the values enacted in health-related information brochures about reading that are distributed to all Swedish parents at various times of their children's lives. The analysis demonstrates how the lack of reading books is enacted as a public health problem that requires prevention and intervention of public healthcare. Health is thus recruited as a stabilising actor in the process of determining the value and importance of reading and where the problem of non-reading of books becomes a private matter for families to solve. The analysis also shows how instances of health-promoting intentions of doing good can in effect be marginalising by viewing specific people as less valuable.